Tracheal dimensions in human fetuses: an anatomical, digital and statistical study - Szpinda, Michał (Springer-Verlag, 2011)
PURPOSE: Rapid advances in perinatal medicine have resulted in increased number of various tracheo-bronchial interventions on fetal and neonatal airways. The present study was performed to compile normative data for external dimensions of the trachea at varying gestational age. MATERIALS AND METHODS: Using anatomical dissection, digital image analysis (NIS-Elements BR 3.0) and statistical analysis (ANOVA, regression analysis), a range of measurements (prebifurcation and bifurcation lengths, proximal and distal external transverse diameters, proximal external cross-sectional area, and external volume) for the trachea in 73 spontaneously aborted fetuses (39 male, 34 female) aged 14–25 weeks was examined. RESULTS: No significant male–female differences were found (P > 0.05). The prebifurcation and bifurcation lengths ranged from 8.14 ± 1.90 to 20.77 ± 0.50 mm and from 2.23 ± 0.25 to 5.77 ± 0.76 mm, according to the functions y = −54.291 + 23.940 × ln (Age) ± 1.681 (R (2) = 0.78) and y = −10.756 + 4.860 × ln (Age) ± 0.731 (R (2) = 0.44), respectively. Their relative growth, expressed as the bifurcation-to-prebifurcation length ratio, was stable from the age of 16 weeks and attained the value 0.22 ± 0.05. The proximal external transverse diameter of the trachea was greater (36 fetuses, 49.3%), smaller (34 fetuses, 46.6%) or similar (3 fetuses, 4.1%), when compared to the distal external transverse diameter. The values for proximal and distal transverse diameters ranged from 2.39 ± 0.04 to 5.20 ± 0.17 mm and from 2.42 ± 0.20 to 4.93 ± 0.08 mm, expressed by the functions: y = −9.659 + 4.574 × ln (Age) ± 0.313 (R (2) = 0.79) and y = −10.897 + 4.984 × ln (Age) ± 0.327 (R (2) = 0.81). The values of proximal external cross-sectional area ranged from 3.38 ± 0.12 to 15.98 ± 1.04 mm(2), according to the linear function y = −11.798 + 1.077 × Age ± 1.463 (R (2) = 0.78). The values of external volume of the trachea ranged from 34.3 ± 11.6 to 370.6 ± 94.1 mm(3) and generated the quadratic function y = −154.589 + 0.858 × Age(2) ± 34.196 (R (2) = 0.87). CONCLUSIONS: The tracheal parameters do not show male–female differences. The developmental dynamics of prebifurcation and bifurcation lengths and proximal and distal external transverse diameters of the trachea follow linear functions dependent on the natural logarithm of fetal age, its external cross-sectional area—according to a linear function, and its external volume—according to a quadratic function.